The Influence of Dividend Policy and Debt Policy on Company Value at PT Arwana Citramulia Tbk Period 2010-2019 - Siti Nur'aidawati; Ifa Nurmasari (Jurnal Mandiri : Ilmu Pengetahuan, Seni, dan Teknologi, 2022)
This study aims to determine the effect of dividend policy and debt policy on firm value. The method used in this study is a quantitative research method. The population in this study is the financial statements of PT Arwana Citramulia Tbk in 2010-2019. The samples in this study are financial statements, income statements notes to financial statements, and stock price reports. The results of the study show that dividend policy has a significant effect on firm value where the value of t count |-2.453| > t table 2.365 and sig value 0.044 < 0.05 and debt policy affects the firm value where the value of t count |-3.821| > t table 2.36462 and sig value 0.007 < 0.05. Meanwhile, simultaneously dividend policy and debt policy have a significant effect on firm value with a value of F count 7.967> F table 4.74 with a sig value of 0.016 <0.05. an adjusted R Square value of 60.8% means that the value of the company is influenced by the independent variable and the remaining 39.2% is influenced by other variables not examined in this study.